2012
DOI: 10.1261/rna.030999.111
|View full text |Cite
|
Sign up to set email alerts
|

Folding of the hammerhead ribozyme: Pyrrolo-cytosine fluorescence separates core folding from global folding and reveals a pH-dependent conformational change

Abstract: The catalytic activity of the hammerhead ribozyme is limited by its ability to fold into the native tertiary structure. Analysis of folding has been hampered by a lack of assays that can independently monitor the environment of nucleobases throughout the ribozyme-substrate complex in real time. Here, we report the development and application of a new folding assay in which we use pyrrolo-cytosine (pyC) fluorescence to (1) probe active-site formation, (2) examine the ability of peripheral ribozyme domains to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 69 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…The difficulty arises in trying to define often short-lived intermediates that are very difficult to identify and quantify. Previous attempts have utilized a range of time-resolved techniques such as footprinting (Sclavi et al 1998;Silverman et al 2000;Shcherbakova et al 2004), scattering (both X-ray and neutron) (Russell et al 2000;Das et al 2003;Perez-Salas et al 2004;Moghaddam et al 2009;Roh et al 2010;Pollack 2011), as well as fluorescence Haller et al 2011;Buskiewicz and Burke 2012;St-Pierre et al 2014;Frener and Micura 2016). Our experiments directly observe continuous changes in the orientations and stacking of the 2AP nucleobases (local events) as well as changes in the global conformational ensemble observed via SAXS during the transition from secondary structure to tertiary folds.…”
mentioning
confidence: 73%
“…The difficulty arises in trying to define often short-lived intermediates that are very difficult to identify and quantify. Previous attempts have utilized a range of time-resolved techniques such as footprinting (Sclavi et al 1998;Silverman et al 2000;Shcherbakova et al 2004), scattering (both X-ray and neutron) (Russell et al 2000;Das et al 2003;Perez-Salas et al 2004;Moghaddam et al 2009;Roh et al 2010;Pollack 2011), as well as fluorescence Haller et al 2011;Buskiewicz and Burke 2012;St-Pierre et al 2014;Frener and Micura 2016). Our experiments directly observe continuous changes in the orientations and stacking of the 2AP nucleobases (local events) as well as changes in the global conformational ensemble observed via SAXS during the transition from secondary structure to tertiary folds.…”
mentioning
confidence: 73%
“…To probe the structural context of C178 in the complex, we employed the fluorescent cytosine analog pyrrolocytosine (PyC). PyC forms a base pair with G that exhibits structural and thermodynamic properties of a normal G•C pair, and its fluorescence is sensitive to its environment (Buskiewicz and Burke, 2012; Tinsley and Walter, 2006; Zhang et al, 2008; Zhang and Wadkins, 2009). To introduce PyC at T-box position 178, we nicked the non-conserved loop of the antiterminator between positions 170 and 171, generating a two-piece variant of T-box 182 .…”
Section: Resultsmentioning
confidence: 99%
“…It suggests that in vitro conditions (Tris/HCl buffer, pH 7.5) are insufficient for effective folding of TLR-extended ribozymes. It has been suggested that at least two-step folding, if inhibited, might become the rate-limiting step explaining low in vitro efficiency [31]. A similar observation was also made for other extended hammerhead ribozymes [28].…”
Section: Figure 8 Comparative In Silico Analysis Of Distances and Angmentioning
confidence: 55%